2012
DOI: 10.1007/s00705-012-1351-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of rabies in Ukraine

Abstract: To investigate the circulation of rabies virus in Ukraine, 78 rabies virus isolates were acquired from 14 states in 2002 and 2008-2010 for characterization. Partial sequences of nucleoprotein (359 nt) and glycoprotein (344 nt) genes were compared with those from neighbouring countries. The analysis identified 39 unique nucleoprotein genes and two geographically distinct RV variants belonging to the cosmopolitan lineage. The Ukrainian samples were similar to the North-East European lineage (NEE) (n = 19) and Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…However, it is known that Romanian sequences showed a high degree of heterogeneity with six different lineages identified and that the RABV group most similar to the NEE group was isolated in Romania's northern regions where the country borders with Ukraine (Turcitu and others 2010). Another very recent study characterised Ukrainian sequences as NEE or Russian group C (Picard-Meyer and others 2012). …”
mentioning
confidence: 99%
“…However, it is known that Romanian sequences showed a high degree of heterogeneity with six different lineages identified and that the RABV group most similar to the NEE group was isolated in Romania's northern regions where the country borders with Ukraine (Turcitu and others 2010). Another very recent study characterised Ukrainian sequences as NEE or Russian group C (Picard-Meyer and others 2012). …”
mentioning
confidence: 99%
“…Keeping in mind that about 2000 cases of rabies occur annually in Ukraine as well as in other republics of the former Soviet Union and in the Balkans (source: http://www.rbe.fli.bund.de/), migration of rabid wildlife to Poland from neighbouring countries is highly probable. As has been suggested by Picard-Meyer et al [21], it is very likely that some or all of the cases of rabies in the Polish provinces Podkarpackie and Lubelskie are due to migration of rabid animals from Ukraine to Poland. In this study, we found more than 99.1 % nucleotide sequence identity in RABV isolates from Poland, Ukraine and Romania.…”
Section: Discussionmentioning
confidence: 93%
“…These results correspond to the geographical distribution of rabies variants in Europe. The NEE group is found in western Russia, Finland, Ukraine, Estonia, Lithuania, Latvia, Romania and Slovakia [3, 16, 21, 26, 31], while the CE group is found in eastern Germany, the Czech Republic, and in Slovenia [3, 16]. The Vistula River, which divides the territory of Poland into two parts, might be a natural border in the distribution of RV variants (NEE and CE), as was previously suggested by Bourhy et al [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study based on glycoprotein gene analyses of 78 rabies virus isolates from Ukraine presented evidence for cross-border movements of rabies virus. 15 In European countries fluctuations have been recorded in bats populations, 14 with high numbers of cases occurring each year. This is a major threat because bats have the fastest transmission rate and can infect animals as well as humans, particularly since bats carrying the virus can live for longer timespans compared to foxes or dogs which die relatively rapidly from the disease.…”
Section: Rabies In Animalsmentioning
confidence: 99%